A ¹⁵N study of the effects of nitrate, ammonium and nitrate plus ammonium nutrition on nitrogen assimilation in Hordeum vulgare - Chadwick, Susan Glynnis (Department of Biological Sciences, 2016)
Bibliography: pages 98-112.